Poster Presentations 2021
DOI: 10.1136/sextrans-2021-sti.195
|View full text |Cite
|
Sign up to set email alerts
|

P051 General practitioners’ (GPs’) knowledge of and attitudes to prescribing pre-exposure prophylaxis for HIV (PrEP): A pilot study

Abstract: with partners outside of one's household. We tried to elucidate motives and barriers for complying with sexual distancing among men who have sex with men (MSM) and the relation with social distancing. Methods In this exploratory qualitative study we interviewed STI clinic visiting MSM during the first COVID-19 lock down using a semi-qualitative questionnaire from March-May 2020. We interviewed both men who complied and did not comply with the sexual distancing measures. The interviews were transcribed using ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The top three barriers that impacted our Australian GPs participants prescribing of PrEP were difficulty identifying clients who would benefit from PrEP, lack of knowledge regarding PrEP, and lack of time to adequately counsel regarding PrEP. These results are comparable with the literature, with the main barriers identified in studies as lack of knowledge regarding PrEP and difficulty identifying clients at risk of HIV (8, 10, 11, 12, 19). Difficulty identifying clients who would benefit from PrEP could be addressed by having GP clinics collect certain demographics as part of client registration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The top three barriers that impacted our Australian GPs participants prescribing of PrEP were difficulty identifying clients who would benefit from PrEP, lack of knowledge regarding PrEP, and lack of time to adequately counsel regarding PrEP. These results are comparable with the literature, with the main barriers identified in studies as lack of knowledge regarding PrEP and difficulty identifying clients at risk of HIV (8, 10, 11, 12, 19). Difficulty identifying clients who would benefit from PrEP could be addressed by having GP clinics collect certain demographics as part of client registration.…”
Section: Discussionsupporting
confidence: 88%
“…Past studies have identified several barriers to PrEP prescribing among GPs. Barriers include lack of knowledge regarding PrEP, inability to identify clients at risk of HIV, and concern that PrEP use may increase the incidence of other STIs (8, 9, 10, 11, 12). An Australian GP questionnaire found the main barriers to PrEP prescribing were lack of experience with antiretrovirals and lack of guidelines for prescription (13).…”
Section: Introductionmentioning
confidence: 99%